Exploring inequalities in health with young people through online focus groups: navigating the methodological and ethical challenges. (12th October 2021) - Woodrow, Nicholas; Fairbrother, Hannah; Crowder, Mary; Goyder, Elizabeth; Griffin, Naomi; Holding, Eleanor; Quirk, Helen
Abstract : Purpose: The use of online focus groups to explore children and young people's (CYP) perspectives of inequalities in health and associated "sensitive" topics raises important ethical and methodological issues to consider. The purpose of the paper is to discuss lessons learnt from navigating the authors' way through some of the key challenges the authors encountered when researching inequalities in health with CYP through online focus groups. Design/methodology/approach: In the paper, the authors draw on reflections and notes from the fieldwork design, public involvement and engagement (PIE) activities and data collection for their research project. Findings: Collecting data online influenced the authors' ability to develop rapport and relationships with CYP and to provide effective support when discussing sensitive topics. The authors note that building activities to develop rapport with participants during recruitment and data collection and establishing clear support and safeguarding protocols helped navigate challenges of online approaches around effective and supportive participant engagement. Originality/value: The paper highlights that despite ethical and methodological challenges of conducting online focus groups with CYP on potentially sensitive topics, the adoption of practical steps and strategies before, during and following data collection can facilitate the safe participation of CYP and generate useful and valid data in meaningful and appropriate ways.